Efforts to Increase Farmers’ Income at Songai Rajah Hamlet through Intensification of Madura Cattle - Alfen, T. Zhila Sheintika; Hayati, Mardiyah (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The agricultural sector, especially rice and corn commodities, has not been able to improve the welfare of farmers in Songai Rajah Hamlet. Farmers have been raising Madura Cattle for generations to survive. However, most of the maintenance of Madura Cattle is only used as a side business which is sold when needed. This study aims to analyze the maintenance management of Madura Cattle and the income level of farmers from the maintenance of Madura Cattle in Songai Rajah hamlet. The data used in this study is primary data derived from observations and interviews with farmers. Data were analyzed using a qualitative descriptive method and a quantitative method. The results showed that farmers had been able to choose good breeders, mating systems, and housing, but had not optimally implemented feed management, disease prevention, and marketing systems. However, the Madura Cattle rearing business in Songai Rajah Hamlet suffers losses due to the low scale of sales and higher costs of labor and feed. Efforts to increase the business of raising Madura Cattle can be done by buying productive age broodstock, mating cows with superior bulls or through artificial insemination (AI) with SNI, and improving the quality of agricultural waste as animal feed through a fermentation process.